Association of Commercial Rice Varieties with Weedy Rice Accessions (Oryza sativa complex) in Pulau Pinang's Rice Granary Area - Zainudin Hussain,; Azmi Man,; Ahmad Sofiman Othman, (Tropical Life Sciences Research, 2011)
Weedy rice (WR) is the most significant weed in direct-seeded fields. It has morphological characteristics similar to those of cultivated rice varieties. WR is more difficult to control than other weeds. We collected WR accessions from four sites within the Pulau Pinang rice growing areas. Thirty six different accessions were collected from each site: B, the northern site; P, the central site; A, the southern site; and N, the southwestern site. Wild rice (Oryza rufipogon), which grows in the sampled areas, was also collected together with four varieties (MR84, MR185, MR211 and MR219) that have been widely planted in these areas for a long period of time. The objective of this study was to compare the morphological characteristics of the WR accessions and cultivated rice. Twenty characteristics were observed for the comparison of WR accessions and rice cultivars. Morpho-matrix analyses allowed the specimens to be grouped to two main groups (A and B), based on a 95% dissimilarity matrix. Group A was subdivided into 7 subgroups consisting of a few WR accessions, wild rice and MR211 (control), and group B was subdivided to 10 subgroups consisting of other WR accessions and the 3 other control varieties. Dendrogram analysis indicated that the morphological traits used in this study were able to differentiate among the WR accessions and the cultivars, except for rice cultivar MR211 and WRA8, which grouped together in subgroup A2. STRUCTURE program analysis indicated that all individuals were distinguishable and were divided into 18 clusters. These results suggest that some genes of the WR accessions have been influenced by commercial varieties. The information gained from this study will be useful to develop rice weed management protocols and good agricultural practices to control WR in the future. Varian padi angin merupakan rumpai yang paling ketara dalam petak sawah yang mengamalkan kaedah tabur terus. Kebanyakan varian padi angin seiras dengan variasi yang ditanam menyebabkan padi angin sukar dikawal. Persampelan telah dijalankan di empat lokasi jelapang padi Pulau Pinang. Sebanyak 36 varian padi angin yang berbeza telah dikenal pasti dari 4 lokasi tersebut: B, lokasi utara; P, lokasi tengah; A, lokasi selatan; dan N, lokasi barat daya. Padi liar (Oryza rufipogon), yang tumbuh di kawasan kajian, dikutip bersama dengan empat varieti yang ditanam secara meluas di sana (MR84, MR185, MR211 dan MR219). Objektif kajian adalah membuat perbandingan ciri morfologi antara padi angin dan varieti ditanam. Sebanyak 20 ciri dikenal pasti untuk perbandingan padi angin dan varieti ditanam. Analisa morpho metrik berjaya mengasingkan kesemua sampel kajian kepada dua kumpulan utama (A dan B) berasaskan 95% ketidaksamaan metrik. Kumpulan A terbahagi kepada 7 subkumpulan yang terdiri daripada beberapa varian padi angin, padi liar dan MR211 (varieti kawalan), sementara itu, kumpulan B terbahagi kepada 10 subkumpulan yang terdiri daripada baki varian padi angin dan 3 lagi varieti kawalan. Analisa dendogram menunjukkan bahawa varian padi angin dan varieti ditanam boleh dibezakan berasaskan ciri-ciri morfologi yang digunakan dalam kajian ini, kecuali MR211 (varieti yang ditanam) dan padi angin WR A8 yang terkumpul bersama dalam subkumpulan A2. Analisa STRUCTURE menunjukkan kesemua individu kajian terbahagi kepada 18 kluster. Hasil kajian menunjukkan sebahagian gen di dalam varian padi angin telah dipengaruhi oleh varieti yang ditanam. Maklumat hasil kajian memberi manfaat dalam pembentukan protokol pengurusan rumpai dan amalan pertanian yang baik untuk pengawalan padi angin pada masa hadapan.